Mirror women, surrealism, and images: self-representation - Chadwick, Whitney; Ades, Dawn; MIT List Visual Arts Center.; Miami Art Museum.; San Francisco Museum of Modern Art. (MIT Press, 1998)
During the 1930s and 1940s, women artists associated with the Surrealist movement produced a significant body of self-images that have no equivalent among the works of their male colleagues. While male artists exalted Woman's otherness in fetishized images, women artists explored their own subjective worlds. The self-images of Claude Cahun, Dorothea Tanning, Leonora Carrington, Frida Kahlo, Meret Oppenheim, Remedios Varo, Kay Sage and others both internalize and challenge conventions for representing femininity, the female body, and female subjectivity. Many of the representational strategies employed by these pioneers continue to resonate in the work of contemporary women artists. The words "Surrealist" and "surrealism" appear frequently in discussions of such contemporary artists as Louise Bourgeois, Ana Mendieta, Cindy Sherman, Francesca Woodman, Kiki Smith, Dorothy Cross, Michiko Kon and Paula Santigo. This book, which accompanies an exhibition organized by the MIT List Visual Art Center, explores specific aspects of the relationship between historic and contemporary work in the context of Surrealism. The contributors re-examine art historical assumptions about gender, identity, and integenerational legacies within modernist and postmodernist frameworks. Questions raised include: how did women in both groups draw from their experiences of gender and sexuality? What do contemporary artistic practices involving the use of body images owe to the earlier examples of both female and male Surrealists? What is the relationship between self-image and self-knowledge. (source: Nielsen Book Data)
Keywords: 1900-1999; 1930-1939; 1940-1949; 1970-1979; 1980-1989; 1990-1999; approches et analyses; arts; arts visuels et médiatiques; cours; discipline; har4600; histoire de l'art; modernisme; postmodernisme; premier cycle; périodes historiques; sexualité; thématiques

Body art: performing the subject - Jones, Amelia (University of Minnesota Press, 1998)
An examination of the social and cultural significance of body art by a major new voice. The past few years have seen an explosion of interest in body art, in which the artist's body is integral to the work of art. With the revoking of NEA funding for such artists as Karen Finley, Tim Miller, and others, public awareness and media coverage of body-oriented performances have increased. Yet the roots of body art extend to the 1960s and before. In this definitive book, Amelia Jones explores body art projects from the 1960s and 1970s and relates their impact to the work of body artists active today, providing a new conceptual framework for defining postmodernism in the visual arts. Jones begins with a discussion of the shifting intellectual terrain of the 1950s and 1960s, focusing on the work of Ana Mendieta. Moving to an examination of the reception of Jackson Pollock's "performative" acts of painting, she argues that Pollock is a pivotal figure between modernism and postmodernism. The book continues with explorations of Vito Acconci and Hannah Wilke, whose practices exemplify a new kind of performance that arose in the late 1960s, one that represents a dramatic shift in the conception of the artistic subject. Jones then surveys the work of a younger generation of artists -- including Laurie Anderson, Orlan, Maureen Connor, Lyle Ashton Harris, Laura Aguilar, and Bob Flanagan -- whose recent work integrates technology and issues of identity to continue to expand the critique begun in earlier body art projects. Embracing an exhilarating mix of methodologies and perspectives (including feminism, queer theory, philosophy, psychoanalysis, and literary theory), this rigorous and elegantexamination of body art provides rich historical insight and essential context that rethinks the parameters of postmodern culture.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; philosophie; postmodernisme; premier cycle; périodes historiques; queer; sciences humaines; sexualité; thématiques; théorie de l'art

Women, art, and society - Chadwick, Whitney (Thames and Hudson, 1990)
L'étude à succès acclamée de l'historienne de l'art Whitney Chadwick remet en question l'hypothèse selon laquelle les grandes femmes artistes sont des exceptions à la règle qui ont « transcendé » leur genre pour produire des œuvres d'art majeures. Tout en présentant certaines des nombreuses femmes depuis le Moyen Âge dont les contributions à la culture visuelle ont souvent été négligées, l'enquête de Chadwick réexamine les œuvres elles-mêmes et la manière dont elles ont été perçues comme marginales, souvent en référence directe au genre. Dans sa discussion sur le féminisme et son influence sur une telle réévaluation, elle aborde également les questions étroitement liées de l'ethnicité, de la classe et de la sexualité.
Keywords: LGBTQIA2+; amériques; cours; discipline; fem1000; genre; har4600; histoire de l'art; histoire et politique; identités LGBTQIA2+; premier cycle; régions géographiques; sexualité; thématiques; états-unis

Le rapt de Ganymède - Fernandez, Dominique (Bernard Grasset, 1989)
"D'après la mythologie grecque, Ganymède était le plus bel adolescent vivant sur la terre. Zeus, le dieu suprême, étant tombé amoureux du jeune homme, prit la forme d'un aigle pour l'enlever et en faire son compagnon dans le ciel. Le rapt de Ganymède est resté le symbole de l'audace nécessaire à un amour qui défie les règles communes. Quand j'étais étudiant, deux mots étaient synonymes : homosexuel et paria. Aux hommes et aux femmes de ma génération a manqué la possibilité de découvrir, chez des modèles que le monde entier admire, une légitimation de goûts que l'opinion publique réprouve sous l'épithète de "contre nature". J'ai voulu montrer, d'une part que la persécution de l'homosexualité à partir du XIXe siècle s'explique par des raisons exclusivement économiques et politiques, d'autre part que certains des plus grands esprits, des meilleurs poètes et romanciers, compositeurs de musique, peintres et cinéastes de tous les temps, de Sapho à Platon, de Whitman à Cavafy, de Melville à Yourcenar, du Caravage à David, de Mozart à Schubert, d'Eisenstein à Visconti, ont tissé un réseau d'oeuvres qui peuvent servir désormais de culture, c'est-à-dire d'exemple et d'encouragement. Bien mieux que les paternes et hypocrites absolutions prononcées depuis cent ans par les psychiatres et psychanalystes, véritable imposture de notre temps, dévoilée ici dans un sottisier réjouissant. D.F." -- Site de l'éditeur
Keywords: 1800-1899; 1900-1999; DIG; LGBTQIA2+; approches et analyses; arts; beaux-arts; cinéma; cours; discipline; europe; his4860; histoire; histoire de l'art; histoire et politique; homophobie; hétérosexisme; identités LGBTQIA2+; littérature homosexuelle; musique; mythologie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; sexualités dissidentes; systèmes d'oppressions; thématiques

The Feminist Critique of Art History - Gouma-Peterson, Thalia; Mathews, Patricia (The Art Bulletin, 1987)
Art criticism and art history from a feminist perspective are recent phenomena, emerging only during the last fifteen years. They have, in their short history, moved from a first generation in which "the condition and experience of being female" was emphasized, to a second generation, beginning in the late 1970s, influenced by feminist criticism in other disciplines and offering a more complex critique of both art and culture through an investigation of the production and evaluation of art and the role of the artist. In this survey, we propose, first, to outline the history of feminist art and art history, then to discuss the interrelated themes in each, and, finally, in the concluding and pivotal sections (IV and V), to discuss various feminist art-critical and art-historical methodologies.
Keywords: 1900-1999; approches et analyses; art moderne; artistes féministes; arts; corps; cours; critique d'art; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; maternité; patriarcat; premier cycle; périodes historiques; représentation; sexisme; sexualité; systèmes d'oppressions; thématiques